Feasibility of determining myocardial infarction type from medical record review - Woo, Ken S (Pulsus Group Inc, 2008)
BACKGROUND: Hospital discharge data are used extensively in health research. Given the clinical differences between ST segment elevation myocardial infarction (STEMI) and non-ST segment elevation myocardial infarction (NSTEMI), it is important that these entities be distinguishable in a medical record. The authors sought to determine the extent to which the type of MI is recorded in medical records, as well as the consistency of this designation within individual records. METHODS: Records of all MI patients admitted to a tertiary care centre in Canada from April 1, 2000, to March 31, 2001, were reviewed. Documentation and consistency of the use of the terms STEMI (Q wave, ST elevation or transmural MI) or NSTEMI (non-Q wave, subendocardial or nontransmural MI) were assessed in the admission history, progress notes, coronary care unit summary and discharge summary sections of each record. RESULTS: Missing data were common; each chart section mentioned MI type in fewer than one-half of charts. When information was combined, it was possible to determine the type of MI in 81.1% of cases. MI type was consistently described as STEMI in 48.7% of cases, and as NSTEMI in 32.4%. Of concern, MI type was discrepant across sections in 10.5% of cases and missing entirely in 8.4% of cases. CONCLUSIONS: The designation of MI cases as STEMI or NSTEMI is both incomplete and inconsistent in hospital records. This has implications for health services research conducted retrospectively using medical record data, because it is difficult to comprehensively study processes and outcomes of MI care if the type cannot be retrospectively determined.